Views of primary Thai teachers toward STREAM education - Prasart Nuangchalerm; Veena Prachagool; Treekom Prommaboon; Juhji Juhji; Imroatun Imroatun; Khaeroni Khaeroni (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study employed survey method for exploring views of teachers toward science, technology, reading, engineering, arts and math science, technology, reading, engineering, arts and math (STREAM) education. Primary teachers were asked their views through questionnaires after STREAM education workshop. Results revealed that teachers have holistic view and having positive view towards STREAM education even though all of them are not science or mathematics teachers. Change in belief and way of practices can allow teachers to do STREAM education in every classroom, design-based learning and creative classroom should be promoted as well. However, holistic view will be more effective into classroom, technology and other supporting learning environments should be prepared.